2007
DOI: 10.1111/j.1478-3231.2007.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative ultrasound for detection of liver metastases from colorectal cancer

Abstract: IOUS is safe, simple to perform and more accurate than pre-operative imaging. It reduces the number of patients subjected to superfluous surgery. The use of IOUS is therefore encouraged during colorectal cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
0
31
0
2
Order By: Relevance
“…3,[9][10][11][12] However, some earlier studies reported a limited clinical value of IoUS. 13,14 Regarding detection of liver lesions, PoI alone attains a sensitivity of 41-68% with transabdominal ultrasound, 60-75% with contrastenhanced CT and 80-85% with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…3,[9][10][11][12] However, some earlier studies reported a limited clinical value of IoUS. 13,14 Regarding detection of liver lesions, PoI alone attains a sensitivity of 41-68% with transabdominal ultrasound, 60-75% with contrastenhanced CT and 80-85% with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that conventional ultrasonography is particularly useful when applied intra-operatively for imaging liver metastases and has been utilised with great success for many years [30][31][32][33]. Propagation of ultrasonic waves is not hindered to any significant degree during liver metastasis surgery because laparotomy is performed prior to data capture.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude récente montrait que seuls trois patients sur 271 (1 %) opérés d'un CCR présentaient des MHS découvertes en peropéra-toires alors même que la TDM multibarrette préopératoire était normal [57]. Cependant, la découverte peropératoire de MHS peut entraîner une modification de la stratégie chirurgicale [58].…”
Section: Pertinence De La Questionunclassified